2017
DOI: 10.1002/14651858.cd006185.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical-assisted training for walking after stroke

Abstract: Analysis 1.2. Comparison 1 Electromechanical-and robotic-assisted gait training plus physiotherapy versus physiotherapy (or usual care), Outcome 2 Recovery of independent walking at follow-up a er study end.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
163
1
14

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(183 citation statements)
references
References 76 publications
5
163
1
14
Order By: Relevance
“…As affirmed recently by Cochrane,35 it is imperative to define the characteristics of patients who may benefit the most from robotic therapy. According to the principle that overground training is the most physiological one, although not always possible, the more is the severity of stroke, the more should be the help and the constraint level provided by the device, as shown in Figure 2.…”
Section: From “Efficacy For All” To “All For Efficacy”mentioning
confidence: 99%
“…As affirmed recently by Cochrane,35 it is imperative to define the characteristics of patients who may benefit the most from robotic therapy. According to the principle that overground training is the most physiological one, although not always possible, the more is the severity of stroke, the more should be the help and the constraint level provided by the device, as shown in Figure 2.…”
Section: From “Efficacy For All” To “All For Efficacy”mentioning
confidence: 99%
“…Cochrane systematic reviews on this topic concluded that “ virtual reality and physiotherapy may have similar effects on gait, balance, and quality of life ” for Parkinson disease [14] or that “ the use of virtual reality and interactive video gaming was not more beneficial than conventional therapy approaches in improving upper limb function ” after stroke [101]. When there is effect of robot-assisted training, the quality of evidence is very low or low for improving arm functions after stroke [102] or moderate for improving independent walking in people after stroke [103]. Researchers who have conducted systematic reviews on the topic suggest that the effectiveness of robot-assisted therapy is more due to the high intensity of training than to the treatment modality [102106]: “ it seems unlikely that therapy provided by robots will lead to better results than therapy provided by humans under the premise that intensity, amount and frequency of therapy are exactly comparable ” [104].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that severely impaired individuals will not be able to tolerate this type of feedback. However, non-ambulatory individuals are currently better served by current forms of RAGT, than ambulatory individuals [10]. Damping fields are likely more appropriate for these higher functioning individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Even with these benefits, there have been mixed results in terms of outcomes [1]–[10]. It should be noted for most studies that showed RAGT to have greater improvements over conventional therapy, RAGT was done in addition to conventional therapy and/or was used in sub-acute populations.…”
Section: Introductionmentioning
confidence: 99%